ANALYSIS ON THE SOURCES OF MERCURY IN SOILS IN THE CHENGDU BASIN, CHINA - Ren L.; Qin B.; Tang W.; Ma Zh.; Hu Y. (My University, 2006)
Mercury is a pollutant of concern due to its toxic and bioaccumulative properties. Studies on the distribution and hazard of mercury in the environment are mainly focused on its forms, toxicity and the environment standard, and progresses and results have been achieved. But these studies in the past were concentrated on the scales of laboratory or smaller districts merely, such as a small unit of mineral area, vegetable base, paddy field, lake, etc. Multi-target regional geochemical survey carried out by China Geological Survey from the 1990s to now is a fundamental and commonweal geological survey, large-scale and systematical inquisition and research were conducted in 19 provinces (or municipalities directly under the Central Government) in the eastern overlay region of China, and the purpose is to provide the basic geochemical data for national economic construction, adjustment of industrial and agricultural structures and sustainable social development.
Keywords: CHENGDU BASIN; MERCURY; MULTIVARIATE STATISTICS; LINEAR REGRESSION; FACTOR ANALYSIS